Leaders Who Create the Happy Workplace - Layraman, Taien (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2014)
All employees spend the day-time with their duties in their offices. If their work and their organizations are enjoyable, they will have a happy life. The productivity made by the employees who are happy will have fewer obstacles. When happy workers are faced with any problems, they can solve them by themselves. Not only the workers create a happy workplace, the leaders do too. The success of leadership depends on the success of an organization. Leaders who create a happy workplace have to learn how to make employees happy at work. Moreover they need to demonstrate that they are excellent leaders by applying the concept of servant leadership. They have to change their attitude from authoritarian leadership to be leaders who serve others. They need to sincerely support their subordinates in all the work, as much work as they do.